EXPLORING FACTORS TO SUCCESSFUL EXCLUSIVE BREASTFEEDING IN PRIMIPAROUS YOUNG MOTHERS IN SAMARINDA: A QUALITATIVE STUDY - Wahyuni, Tri; Hakim, Lukman; Ernawati, Rini; Andriani, Dwi Astri (NurseLine Journal, 2026)
Background: Breast milk is the best food for babies, as it contains the optimal nutritional content. The WHO emphasizes the importance of exclusive breastfeeding for the first six months to support infant growth and development, without any additional food. The Quran, in Surah Al-Baqarah, verse 233, recommends breastfeeding for two years for mothers who wish to establish a sufficient milk supply for their babies. Providing exclusive breastfeeding requires strong efforts from the mother as well as support from her partner, family, and health workers. Objective: This study aims to explore and understand the factors that contribute to mothers' success in exclusively breastfeeding their children. Method: Qualitative research was conducted among 12 primiparous mothers in Samarinda who successfully breastfed their infants. Data collection involved in-depth interviews and observations with first-time mothers who had successfully breastfed their babies, aged 6-12 months, followed by thematic analysis. Result: Four themes emerged: knowledge about exclusive breastfeeding, support system, religious beliefs, and economic factors. Exclusive breastfeeding was successful in all respondents. Mothers' knowledge of exclusive breastfeeding, support from their partners and health workers, understanding of the Quran, and family economic factors were the determinants of successful breastfeeding. Conclusion: There were many factors to successful breastfeeding among young mothers with their first infant. The specific findings on the success of exclusive breastfeeding, including an understanding of the meaning of Al-Baqarah 233 in relation to the perfection of breastfeeding. Specific and appropriate interventions for primiparous mothers are needed to support the success of providing exclusive breastfeeding.